By poles which may Alter Political Landscape of U.P. and Bihar in 2019 Indian General Elections - Sehgal, M. L. (Advances in Social Sciences Research Journal, 2018)
The present study is an attempt to give an idea of the number of parliamentary constituencies which may change hands between the N.D.A. and the United Opposition if it comes to Modi versus the REST in 2019 Lok Sabha elections. It, now, looks certain, especially when the B.S.P., after forgetting its personal and political animosity, extended its whole hearted support to S.P. in the Gorakhpur and Phulpur Lok Sabha by poles to be followed by the United Opposition (B.S.P., S.P and UPA) in Kairana along with the support of the Peace Party and the other Smaller Parties especially the NISHAD Party in U.P. This resulted in the consolidation of Muslims (19.26%), Yadavs (14.0%), Dalits (21.1%) and Nishads-a politically important O.B.C. class (5.0%) in U. P. In Bihar, despite Lalu Prasad’s conviction, his son Tejashwi Yadav has come of his age to lead R.J.D and was able to retain Araria parliamentary seat even in the face of stiff opposition from the ruling NDA. These two states, together, have served as a basket full of votes for N.D.A. in 2014 by sending 104 out of the120 Law Makers in India’s Lower House of Parliament of 543strength. So both the B. J.P. and the Opposition will have to put their best foot forward-B.J.P for staying in power and Opposition for snatching the power in the coming general elections as the road to attain power in Delhi passes through U.P. and Bihar.